TANGGAPAN ANATOMIS AKAR DAN PERTUMBUHAN CABAIRAWIT (Capsicum frutescens L.) TERHADAP LIMBAH CAIR TAHU - , UKHTI TYAS ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia as a developing country has many industrial factories that carelessly dispose its liquid waste to the environment. Tofu industry is the one which produce organic liquid waste in its disposal system. Actually that liquid waste not only can be used for making of biogas and nata de soya, but also containing organic fertilizer in liquid form. Cayennepepper (Capsicum frutescens L.) is usually used to be herbs and food flavoring, besides being the main commodity of vegetables for domestic and big industries. Thus, this research was aimed is to know the effect of tofu liquid waste on cayenneroot anatomic and plantgrowth.This research used 5 different concentration of tofu liquid waste